Sol, mixture, coated film, method for preparing sol, and method for preparing coated film
Patent Information
- Application Number
- CN202310759865.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-28
- Filing Date
- 2023-06-26
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-06-26
AI Technical Summary
Existing sol solutions have poor dispersion stability in the presence of water, making them difficult to store for long periods. Furthermore, their coating performance is poor when mixed with aqueous sol solutions, making it difficult to form a uniform composite inorganic oxide film.
By adding metal alkoxide condensates, α-substituted β-diketones, water-soluble organic solvents, inorganic acids, and organic acids to the sol solution, and adjusting the proportions and order of addition of each component, a stable sol solution is formed. This sol solution can maintain dispersion stability after mixing with aqueous sol solutions and form a uniform composite inorganic oxide film.
It improves the dispersion stability and coating performance of sol solutions in aqueous conditions, and can form a uniform composite inorganic oxide film after mixing with aqueous sol solutions, thus solving the problem of deterioration in dispersibility and coating performance.
Smart Images

Figure BDA0004304434750000051 
Figure BDA0004304434750000291 
Figure BDA0004304434750000301
Abstract
Description
Technical Field
[0001] This invention relates to sol solutions, mixtures, coated films, methods for preparing sol solutions, and methods for preparing coated films. Background Technology
[0002] Metal oxide thin films are functional materials suitable for applications such as optical films, antireflective films, photocatalysts, transparent conductive films, or surface protective films. Typically, metal oxide thin films are formed using chemical vapor deposition (CVD), physical vapor deposition (PVD), or sol-gel methods. In the sol-gel method, a colloidal liquid is prepared by hydrolysis with water and condensation reaction using metal alkoxides or metal chlorides as raw materials.
[0003] The sol-gel method, which uses an organic sol containing an organic solvent as the main solvent, is a method for preparing many kinds of metal oxide and composite metal oxide sols. The advantages of the prepared sols include, for example, ease of coating due to the high wettability of the organic solvent on the substrate. In particular, the sol-gel method is advantageous in its ability to easily form uniform films for thin film formation. However, when the organic sol contains a large amount of water in the solvent, it is prone to excessive deterioration of dispersibility or gelation through aggregation between condensates. Therefore, a problem with the sol-gel method is that organic sols in a stable dispersed state are difficult to store for long periods.
[0004] In recent years, the application of forming composite metal oxide films containing multiple elements has been increasing, and it is desirable to obtain liquids by mixing multi-element inorganic particle slurries. Japanese Patent Application Publication No. 2011-073893 describes how the long-term durability of the dispersion state of an aqueous nanoparticle zirconia sol can be improved by using glucose or sucrose as a dispersant when mixed with a hydrophilic solvent. Furthermore, Japanese Patent Application Publication No. 2007-51053 describes how metal oxide nanoparticles can be stably dispersed in an organic solvent by using a surfactant as a dispersant. Additionally, Japanese Patent Application Publication No. H10-259007 describes a coating solution for forming a film containing a metal alkoxide, a metal alkoxide hydrolysate, and a β-diketone.
[0005] However, the sol solutions in each of Japanese Patent Application Publication Nos. 2011-073893 and 2007-51053 have the following risk: dispersant residues may remain even after baking. In Japanese Patent Application Publication No. H10-259007, the dispersion stability deteriorates when water is added to the coating solution, thus posing a risk of deteriorated coating performance or difficulty in obtaining a uniform coating film.
[0006] The object of this invention is to provide a sol solution that exhibits excellent dispersion stability even when the sol solution contains water, is mixable with existing aqueous sol solutions in any proportion, and can readily prepare uniform composite inorganic oxide films with good coating properties. Furthermore, another object of this invention is to provide mixtures and coating films using the sol solution, methods for preparing the sol solution, and methods for preparing the coating film. Summary of the Invention
[0007] The inventors of this invention have discovered that the above-mentioned objective can be achieved by applying a specific stabilizer and two acids to a granular condensate obtained by condensing metal alkoxides in a sol solution. Therefore, the inventors have obtained this invention.
[0008] In other words, the sol solution of the present invention comprises the following components: metal alkoxide condensate; α-substituted β-diketone; and water-soluble organic solvent, wherein the sol solution further comprises inorganic acid and organic acid.
[0009] Other features of the invention will become clear from the following description of exemplary embodiments with reference to the accompanying drawings. Attached Figure Description
[0010] Figure 1 The results of X-ray diffraction (XRD) analysis of zirconium oxide powder obtained by sintering the sol solution of Example 1 in an electric furnace at 300°C for 2 hours are shown. Detailed Implementation
[0011] The following describes embodiments of the present invention, but the present invention is not limited to the following embodiments.
[0012] Sol-gel solution
[0013] The sol solution of the present invention comprises the following components: a metal alkoxide condensate; an α-substituted β-diketone; and a water-soluble organic solvent, and the sol solution further comprises inorganic and organic acids. The sol solution of the present invention may also be referred to as an "organic sol solution." Various additives, such as pH adjusters and viscosity modifiers, may be suitably added to the sol solution of the present invention.
[0014] The sol solution of the present invention can be used to form a film alone, or it can be used as a mixture with water or an aqueous sol solution to form a film. When the sol solution of the present invention is used as a mixture, it can be applied stably without a decrease in dispersibility (e.g., turbidity). Furthermore, when the sol solution contains multiple metal elements, or when the mixture obtained by mixing the sol solution and an aqueous sol solution contains multiple metal elements, a composite inorganic oxide film can be formed by using any of these liquids. For example, the following situation can be given: the metal alkoxide condensate in the sol solution contains one metal element (a first metal element), and the metal alkoxide condensate in the aqueous sol solution to be mixed contains a second metal element different from the first metal element.
[0015] [1] Metal alkoxide condensate
[0016] (a) Metal alkoxides
[0017] The metal alkoxide used in this invention is represented by the following formula (a):
[0018] M(OR) m O n …(a)
[0019] In equation (a), M represents a metallic element in groups 3 to 15 of the periodic table, R represents a saturated or unsaturated hydrocarbon group, "m" represents an integer from 2 to 5, and "n" represents 0 or 1.
[0020] Examples of metallic element M include aluminum, silicon, scandium, titanium, vanadium, manganese, iron, cobalt, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, indium, tin, antimony, lanthanum, tantalum, tungsten, and iridium. Preferred examples include aluminum, silicon, titanium, vanadium, manganese, zinc, yttrium, zirconium, niobium, molybdenum, indium, tin, tantalum, and tungsten.
[0021] Examples of metal alkoxides to be preferred include: aluminum triisopropoxy, aluminum tri-n-propoxy, aluminum triisobutoxy, aluminum tri-n-butoxy, aluminum tri-sec-butoxy, tetraethoxysilane, tetra-isopropoxysilane, tetra-n-propoxysilane, tetraisobutoxysilane, tetra-n-butoxysilane, tetra-sec-butoxysilane, tetramethoxytitanium, tetraethoxytitanium, tetra-n-propoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetraisobutoxytitanium, tetraisobutoxytitanium, tetra-sec-butoxytitanium, vanadium trimethoxy oxide, vanadium triethoxy oxide, vanadium tri-n-propoxyvanadium oxide, vanadium triisobutoxyvanadium oxide, vanadium tri-n-butoxyvanadium oxide, vanadium trisec-butoxyvanadium oxide, and so on. Isopropoxy manganese, diethoxy zinc, triethoxy yttrium, triisopropoxy yttrium, tetramethoxy zirconium, tetraethoxy zirconium, tetraisopropoxy zirconium, tetran-propoxy zirconium, tetraisobutoxy zirconium, tetran-butoxy zirconium, tetrasec-butoxy zirconium, pentaethoxy niobium, pentaisopropoxy niobium, penta-butoxy niobium, pentaisobutoxy niobium, pentasec-butoxy molybdenum, pentaethoxy molybdenum, triisopropoxy indium, tetraethoxy tin, tetraisopropoxy tin, tetran-butoxy tin, pentamethoxy tantalum, pentaethoxy tantalum, pentaisopropoxy tantalum, penta-propoxy tantalum, pentaisobutoxy tantalum, penta-butoxy tantalum, pentasec-butoxy tantalum and pentaethoxy tungsten.
[0022] (b) Condensate
[0023] A condensate of a metal alkoxide is obtained by hydrolyzing the metal alkoxide represented by formula (a) in an organic solvent in the presence of water. One or more of the metal alkoxides represented by formula (a) may be used in the formulation.
[0024] The metal element content "a" [mass %] of the metal alkoxide condensate is preferably within 0.770 ≤ a ≤ 6.20, more preferably within 0.800 ≤ a ≤ 6.00, and even more preferably within 1.00 ≤ a ≤ 5.00, relative to the total amount of the sol.
[0025] (c) Degree of condensation of the condensate
[0026] The condensate is preferably an incomplete condensate where the condensation process does not reach 100%. The degree of condensation of the condensate in the sol solution is preferably 25% or more and 70% or less, more preferably 30% or more and 60% or less. When the degree of condensation is 25% or more, sufficient film strength is easily obtained. Furthermore, when the degree of condensation is 70% or less, gelation in the solution state can be prevented, thus ensuring film-forming performance.
[0027] (d) Particle diameter of the condensate
[0028] The condensate of the metal alkoxide is granular (hereinafter sometimes simply referred to as "granular condensate"). The median diameter of the granular condensate is preferably 1 nm or more and 100 nm or less, more preferably 1 nm or more and 50 nm or less, and most preferably 2 nm or more and 20 nm or less. The median diameter can be determined by dynamic light scattering in the sol solution. When the median diameter is 1 nm or more, the metal alkoxide exhibits moderate condensation and shows almost no uneven distribution or cracks during film formation, thus resulting in a uniform film. Furthermore, when the median diameter is 100 nm or less, the dispersion stability is almost not reduced when the sol solution is mixed with water or an aqueous sol, thus achieving film transparency after film formation.
[0029] A specific method for measuring the median diameter can be, for example, using a NANOTRAC FLEX (manufactured by Microtrac BELCorp., employing a 50% cumulative value from the volume distribution) to measure using laser scattering. For instance, in a sol containing a zirconium alkoxide condensate and 2-propanol as the main solvent, the median diameter can be determined according to the following procedure: Using the prepared sol as a sample, the particle diameter is measured five times using the NANOTRAC FLEX under the conditions of a particle refractive index of 2.21, a solvent refractive index of 1.38, and a measurement time of 30 seconds. The average value is taken as the median diameter of the metal alkoxide condensate.
[0030] [2] α-substituted β-dione
[0031] In the hydrolysis and condensation of metal alkoxides to synthesize metal compound sols, α-substituted β-diketones act as stabilizers to inhibit the aggregation of granular condensates. α-substituted β-diketones are preferably represented by the following general formula (b). In formula (b), R1, R2, and R3 each represent an alkyl group having one or more but less than three carbon atoms, and may be the same as or different from each other.
[0032]
[0033] Examples of α-substituted β-diketones include 3-methyl-2,4-pentanedione, 4-methyl-3,5-heptanedione, 3,5-dimethyl-2,4-hexanedione, and 3-ethyl-2,4-pentanedione. 3-methyl-2,4-pentanedione is particularly preferred. When the number of carbon atoms in R1, R2, and R3 is relatively small, residues in the film after formation are avoided, thus resulting in satisfactory film properties. Furthermore, when the number of carbon atoms in R3 is zero, the dispersion stabilization effect on metal compound particles in the liquid becomes insufficient, thus posing a risk that the particle diameter of the granular condensate may increase.
[0034] To maintain a dispersed state, the metal element content of the metal alkoxide and the content of the α-substituted β-diketone preferably satisfy the following equation (4):
[0035] 0.20≤a / d≤1.1 (4)
[0036] Wherein: "a" represents the metal element content [mass%] of the metal alkoxide condensate relative to the total amount of the sol; and "d" represents the content [mass%] of the α-substituted β-diketone relative to the total amount of the sol.
[0037] a / d is more preferably within the range of 0.25 ≤ a / d ≤ 1.1.
[0038] When the a / d ratio is 0.20 or higher, a coating film can be formed without leaving the α-substituted β-diketone in the film after film formation, and the influence of the α-substituted β-diketone on the optical properties of the coating film can be avoided. Furthermore, when the a / d ratio is 1.1 or lower, the ratio of the α-substituted β-diketone to the metal alkoxide is sufficiently large to suppress aggregation between particulate condensates, thus maintaining a dispersed state in the sol solution.
[0039] [3] Water-soluble organic solvents
[0040] Water-soluble organic solvents are preferably organic solvents that do not undergo phase separation but rather mix with water. Even if the solubility of a single organic solvent in water is poor, two or more organic solvents can be used, as long as sufficient water solubility is obtained. Examples of water-soluble organic solvents include alcohol solvents, glycol solvents, glycol ether solvents, ether solvents, and ketone solvents. Water-soluble organic solvents preferably contain at least one selected from the following: alcohol solvents; glycol solvents; glycol ether solvents; ether solvents; and ketone solvents, and more preferably contain alcohol solvents, glycol solvents, or glycol ether solvents. Preferred examples include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, tert-butanol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl carbitol, ethyl carbitol, butyl carbitol, propylene glycol monomethyl ether (1-methoxy-2-propanol), and propylene glycol monoethyl ether (1-ethoxy-2-propanol). More preferred examples include methanol, ethanol, 1-propanol, 2-propanol, tert-butanol, methyl cellosolve, ethyl cellosolve, butyl cellosolve, methyl carbitol, ethyl carbitol, propylene glycol monomethyl ether (1-methoxy-2-propanol), and propylene glycol monoethyl ether (1-ethoxy-2-propanol). These organic solvents can be used alone or in combination.
[0041] Furthermore, regarding the formation of the coated film, it is preferable to add an organic solvent with a normal boiling point of 130°C or higher at a ratio of 10% by mass or more, preferably 20% by mass or more, and more preferably 30% by mass or more relative to the total amount of organic solvent. When the ratio of the solvent with a boiling point of 130°C or higher is 10% by mass or more, the ratio of the solvent with a rapid evaporation rate becomes smaller, and therefore almost no film defects are generated when forming the film.
[0042] Ideally, the content of water-soluble organic solvent in the sol solution is 40% by mass or more, preferably 50% by mass or more, and more preferably 60% by mass or more, relative to the total amount of the sol solution. In this invention, solvents other than water-soluble organic solvents can also be used in combination, and in this case, when the content of water-soluble organic solvents falls within the above-mentioned range, the reduction in film uniformity during film formation can be suppressed. When the content of water-soluble organic solvents is 40% by mass or more, wettability of the substrate can be more easily ensured during coating, and therefore, uneven coating occurs almost non-existent.
[0043] [4] Inorganic acids
[0044] Any inorganic acid can be used, as long as it is an acid that catalyzes the formation of condensates through the hydrolysis of metal alkoxides. Specifically, the inorganic acid preferably includes one or more selected from: hydrochloric acid; sulfuric acid; nitric acid; and phosphoric acid, more preferably hydrochloric acid.
[0045] The metal element content and inorganic acid content of the metal alkoxide condensate preferably satisfy the following relationship (1):
[0046] 4.0×10 -5 ≤b / a≤3.5×10 -4 (1)
[0047] Wherein: "a" represents the metal element content [mass%] of the metal alkoxide condensate relative to the total amount of the sol; and "b" represents the content [mass%] of the inorganic acid relative to the total amount of the sol.
[0048] To moderately advance the hydrolysis and condensation reactions of metal alkoxides, b / a is more preferably at 4.6 × 10⁻⁶. -5 ≤b / a≤3.2×10 -4 Within, a more preferred value is 7.0×10. -5 ≤b / a≤2.0×10 -4 Furthermore, the content of inorganic acid "b" is preferably below 9.10 × 10⁻⁶. -5 ≤b≤7.40×10 -4 Within, it is more preferably located at 9.10×10 -5 ≤b≤6.00×10 -4 Within, a more preferred value is 1.00×10.-4 ≤b≤4.00×10 -4 Inside.
[0049] When b / a is 4.0 × 10 -5 When the above conditions are met, the hydrolysis and condensation reactions of metal alkoxides proceed easily, reducing the likelihood of uneven distribution or cracks during film formation and resulting in a more uniform film. Furthermore, when b / a is 3.5 × 10⁻⁶... -4 Under these conditions, the particle size distribution of the condensate remains almost unchanged. Furthermore, coarse particles are almost nonexistent. Additionally, the dispersion stability is hardly reduced when water or an aqueous sol is added.
[0050] [5] Organic acids
[0051] The organic acid is not particularly limited, but is preferably an organic acid having one or more carboxyl groups and less than six carbon atoms. Specific examples include acetic acid, formic acid, citric acid, malic acid, lactic acid, succinic acid, propionic acid, glycolic acid, malonic acid, glutaric acid, and tartaric acid. The organic acid preferably includes at least one selected from the group consisting of acetic acid, formic acid, citric acid, malic acid, lactic acid, succinic acid, propionic acid, glycolic acid, malonic acid, glutaric acid, and tartaric acid; more preferably, it includes at least one or more selected from the group consisting of acetic acid, formic acid, citric acid, malic acid, lactic acid, and succinic acid; and even more preferably, it contains acetic acid or formic acid.
[0052] The organic acid is added to improve the dispersion stability of the metal alkoxide condensate. The inventors of this invention have conducted in-depth research on compounds that can stably coordinate with the condensate to maintain its dispersibility in both hydrophobic and hydrophilic solvents, thereby addressing the problem of a significant decrease in dispersion stability when a sol containing the metal alkoxide condensate is mixed with a highly hydrophilic solvent (e.g., water). As a result, the inventors discovered that this problem can be solved by adding an organic acid, preferably an organic acid with a low acid dissociation constant, to an inorganic acid.
[0053] As described above, inorganic acids are used to hydrolyze metal alkoxides to produce condensates. The inorganic acids are added to the sol as is, and upon the addition of water, the degree of acid dissociation tends to become higher than before the addition of water. Therefore, further hydrolysis of the metal alkoxides retained in the condensate particles is tended to be promoted, and thus aggregation occurs between the condensate particles, resulting in coarse particles and turbidity.
[0054] In contrast, when organic acids are added, these acids (especially those with low dissociation constants) can exist in the sol solution with a high affinity for the condensate particles. Furthermore, when the sol solution is mixed with water, acid dissociation in organic acids is generally more difficult than in inorganic acids, thus the organic matter is stably coordinated near the condensate particles. Additionally, the presence of organic acids near the condensate particles can also inhibit further hydrolysis of alkoxides remaining within the condensate particles.
[0055] Furthermore, in this invention, the α-substituted β-diketone is used as a dispersion stabilizer for the condensate particles, thus the organic acid has an affinity for the hydrophobic structural portion of the α-substituted β-diketone coordinated with the condensate particles. Therefore, even when the sol medium changes from highly hydrophobic to hydrophilic through mixing with water, generally, the acid dissociation of inorganic acids is more preferential than that of organic acids, and thus it is considered that the dissociation of organic acids proceeds moderately with the increase of the hydrophilicity of the medium. Therefore, it can be considered that the coordination between the condensate particles and the α-substituted β-diketone can be stably maintained. When no organic acid is used, even if the α-substituted β-diketone can stably coordinate with the condensate in a hydrophobic medium, the coordination of the α-substituted β-diketone becomes unstable in a medium whose hydrophilicity increases, for example, through mixing with water, thereby causing the condensate particles to easily aggregate.
[0056] The metal element content and organic acid content of the metal alkoxide condensate preferably satisfy the relationship between the following equations (2) and (3):
[0057] 0.020≤c≤20 (2)
[0058] 0.025≤c / a≤3.3 (3)
[0059] Wherein: "a" represents the metal element content [mass%] of the metal alkoxide condensate relative to the total amount of the sol; and "c" represents the organic acid content [mass%] relative to the total amount of the sol.
[0060] The content of organic acid "c" is more preferably within 0.020 ≤ c ≤ 15, and most preferably within 0.10 ≤ c ≤ 10. Furthermore, c / a is more preferably within 0.030 ≤ c / a ≤ 3.3, and most preferably within 0.050 ≤ c / a ≤ 2.5. These ranges are desirable because the dispersion stability is further improved when water is added.
[0061] When the content of organic acid “c” falls within the range of equations (2) and (3), the conditions under which the organic acid has an affinity for the condensate particles become stable. Therefore, when the sol is mixed with, for example, water, the particle size distribution of the condensate particles hardly widens. Consequently, coarse particles are hardly observed.
[0062] The content of α-substituted β-diketones and the content of organic acids preferably satisfy the following relationship (5):
[0063] 3.0×10 -3 ≤c / d≤5.0 (5)
[0064] Wherein: “c” represents the content of organic acids relative to the total amount of sol [mass%]; “d” represents the content of α-substituted β-diketones relative to the total amount of sol [mass%].
[0065] The c / d ratio is more preferably within the range of 0.030 ≤ c / d ≤ 5.0, and most preferably within the range of 0.050 ≤ c / d ≤ 4.0. These ranges are desirable because the dispersion stability is further improved upon the addition of water.
[0066] When c / d falls within the range of equation (5), the conditions under which α-substituted β-diketones have an affinity for organic acids become stable, and therefore the particle size distribution of the condensate particles hardly widens when the sol is mixed with, for example, water. Thus, almost no coarse particles appear.
[0067] <Mixed Solution>
[0068] The mixture of the present invention contains the sol solution of the present invention and water. The water in the mixture may be water to be added to the aqueous sol solution. The pH value of the mixture is preferably 2.00 or higher and 7.00 or lower, more preferably 2.50 or higher and 7.00 or lower, and even more preferably 3.00 or higher and 6.50 or lower. When the pH value is 2.00 or higher, almost no deterioration occurs, such as erosion of the substrate surface during film formation, and when the pH value is 7.00 or lower, almost no decrease in dispersion stability occurs when water or aqueous sol solution is added.
[0069] The mixture allows for improved dispersion stability of the condensate particles in the sol solution of the present invention, as well as improved processability in the coating step, thus enabling the acquisition of a coated film with excellent properties. Known methods can be employed as a method for preparing the mixture; therefore, the mixture can be prepared by mixing water or an aqueous sol solution or any solvent from various solvents into the sol solution of the present invention.
[0070] <Coated film and method for preparing coated film]
[0071] The coating film of the present invention is formed by heating the sol or mixture of the present invention. Furthermore, the method for preparing the coating film of the present invention includes, in the following order: a coating step of applying the sol or mixture of the present invention onto a substrate; and a heating step of heating the substrate at a temperature equal to or less than the glass transition temperature of the substrate.
[0072] [1] Application steps
[0073] The substrate simply needs to be able to withstand the heating process. Examples of substrates that can be used include hard glass, soft glass, plastic, semiconductor substrates (e.g., silicon), or metal plates. Furthermore, each of these substrates may have an inorganic film on its surface. For example, an inorganic film formed on a semiconductor substrate can be used as the substrate, and a coating film can be formed on its surface.
[0074] As application methods, wet methods such as dipping, spin coating, spraying, printing, and flow coating are given, for example. Application methods are not limited to these methods.
[0075] [2] Heating steps
[0076] In the heating step, the condensation reaction of the condensate in the sol or mixture is promoted by heating the substrate that has been coated in the coating step, thereby forming a metal oxide, and a film can be formed by drying the coating film.
[0077] <Preparation method of sol solution>
[0078] The method for preparing the sol solution of the present invention includes: a condensation step in which an inorganic acid is added to a reaction solution obtained by mixing a metal alkoxide and an α-substituted β-diketone with a water-soluble organic solvent to condense the metal alkoxide; and an organic acid addition step in which an organic acid is added to the reaction solution after the condensation step. The amount of each component added is preferably set to such that the content of that component in the sol solution falls within the range described in the "sol solution" section.
[0079] The preparation method of the present invention may include the step of appropriately adding various additives (e.g., pH adjusters and viscosity improvers) in addition to the steps described above. When adding the additives, it is preferable to add them after the organic acid addition step, because the dispersion stability of the condensate particles can be easily maintained.
[0080] [1] Condensation steps
[0081] As a method for mixing a metal alkoxide and an α-substituted β-diketone with a water-soluble organic solvent, a known method can be used, an example of which is as follows: the metal alkoxide and the α-substituted β-diketone are added sequentially to the water-soluble organic solvent, followed by stirring and mixing. Subsequently, an inorganic acid is added to the reaction solution. In the method of adding the inorganic acid, only the inorganic acid may be added, but the method is preferably a method of gradually adding the inorganic acid as a solution obtained by adding the inorganic acid to the water-soluble organic solvent and stirring the mixture. The above method is desirable because the heating is suppressed when the inorganic acid is added, and because the hydrolysis reaction can proceed uniformly. Thereafter, the hydrolysis reaction and condensation reaction of the metal alkoxide are carried out to form a granular condensate. In this case, it is preferable to carry out the reaction under heating. The reaction temperature is preferably above 50°C and below 120°C. The reaction can also be carried out in a closed container at a reaction temperature equal to or above the boiling point of the water-soluble organic solvent.
[0082] [2] Organic acid addition steps
[0083] As a method for adding an organic acid to the reaction solution in which granular condensates are formed during the condensation step, known methods can be used, and it is preferable to add the reaction solution while stirring. Furthermore, when adding the organic acid, it is desirable to do so under conditions where the reaction solution has cooled to room temperature. Subsequently, since the affinity of the organic acid for the granular condensates improves, it is desirable to perform heat treatment of the reaction solution. Heat treatment is performed at a temperature preferably above 20°C and below 100°C, more preferably above 30°C and below 60°C. The heat treatment period is preferably 5 minutes or more and 1 hour or less. In the organic acid addition step, in addition to the organic acid, an α-substituted β-diketone can also be added as a stabilizer.
[0084] [Example]
[0085] The invention is described in more detail below with reference to examples and comparative examples. The invention is not limited to the examples described below without departing from its spirit. The terms "part" and "%" in the description of component quantities are by mass unless otherwise stated.
[0086] In Tables 1 to 3, the upward arrows indicate that the content is the same as the previous column. Furthermore, in Tables 1 to 3, the content of components other than the metal, inorganic acid, organic acid, α-substituted β-done, and water-soluble organic solvent in metal alkoxide condensates can be determined by subtracting "a+b+c+d+water-soluble organic solvent content" from 100. For example, this includes the content of structural moieties other than the metal in metal alkoxide condensates.
[0087] [Example 1]
[0088] <Contraction Steps>
[0089] As shown in Table 1, 10.0 parts of a tetra-n-butoxyzirconium solution in butanol (tetra-n-butoxyzirconium concentration: 85 wt%, metal alkoxide), 19.1 parts of 2-propanol (water-soluble organic solvent) and 1.9 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel and the contents were stirred at 130 rpm. The reaction vessel was equipped with a thermometer, a dropping funnel and a stirring device.
[0090] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 44.7 parts of 2-propanol (water-soluble organic solvent), and 28.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0091] <Organic Acid Addition Steps>
[0092] As shown in Table 1, acetic acid (an organic acid) was added dropwise to the reaction solution after the condensation step to a concentration of 0.1%, while the reaction solution was stirred at 130 rpm. Heat treatment was performed for 30 minutes with continued stirring, and the temperature was maintained at 30°C in an oil bath. Thus, a sol solution containing granular incomplete condensates of zirconium alkoxides was obtained. The content of each substance in the "Organic Acid Addition Step" column of Table 1 is related to the sol solution.
[0093] The X-ray diffraction (XRD) analysis results of the zirconia powder obtained by sintering the sol solution in an electric furnace at 300℃ for 2 hours are as follows: Figure 1 As shown.
[0094] <Preparation of Coated Film>
[0095] The substrate (ground glass slide, material: soda glass, rectangular, 3t × 40 × 40 mm) was ultrasonically cleaned for 30 minutes using 2-propanol and then dried. The resulting product was then ozone cleaned for 10 minutes, and dust was removed by spraying to clean the substrate. This yielded a glass substrate for coating. 0.3 ml of the sol solution was applied to the glass substrate using a spin coater (product name: "1H-D7", manufactured by Mikasa Corporation) at 2685 rpm for 60 seconds, and the resulting product was baked in an electric furnace at 300°C for 2 hours. This produced a coating film formed from the sol solution.
[0096] In addition, a coating film formed by the mixture was prepared using 0.3 ml of the mixture in the same manner as described above. The mixture was obtained by mixing 1 part of aqueous silica sol (product name: "ST-OXS", manufactured by Nissan Chemical Industries, Ltd.) into 1 part of sol solution.
[0097] <Evaluation>
[0098] The sol and coating film were evaluated as described below. The results are shown in Table 4.
[0099] (Evaluation 1: Median diameter of granular condensate)
[0100] The median diameter of the granular condensate in the sol solution was measured using a nanoparticle diameter measuring instrument (product name: "NANOTRAC FLEX", manufactured by Microtrac BELCorp., volume distribution method). Known values for the metal oxide and the main solvent were used as numerical values for the particle refractive index and the solvent refractive index, respectively.
[0101] (Evaluation 2: pH value after adding water)
[0102] Add the amounts of water shown in Table 4 to 1 part of the sol solution, and then measure the pH value using a portable pH meter D-54 (manufactured by Horiba Seisakusho).
[0103] (Evaluation 3: Dispersibility after adding water)
[0104] Add the amounts of ion-exchanged water shown in Table 4 to one part of the sol solution. Then store the resulting product in a refrigerator (5°C) and observe it visually. For the time period during which no precipitation or gelation occurs, evaluate the dispersibility according to the following criteria.
[0105] A: More than 1 month
[0106] B: More than 1 week but less than 1 month
[0107] C: More than 1 day but less than 1 week
[0108] D: Less than 1 day
[0109] (Evaluation 4: Film-forming properties of the coated film)
[0110] The film thickness was measured using a reflectance spectroscopy film thickness gauge FE-3000 (manufactured by Otsuka Electronics Co., Ltd.), and the appearance of the film was visually observed. Reflectance spectra were measured at five points (four near the center and corners), and fitted using the least squares method. The film thickness was thus determined. The change in film thickness [%] was represented by (maximum - minimum) / (average) × 100, and the film formation performance was evaluated according to the following criteria.
[0111] A: It can form a uniform film (the film thickness variation is less than 30%).
[0112] B: Localized differences in membrane thickness exist (membrane thickness variation is greater than 30% but less than 100%).
[0113] C: There are uncoated areas (these areas can be visually observed, or the change in film thickness is more than 100%).
[0114] [Example 2]
[0115] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment time was changed to 5 minutes in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0116] [Example 3]
[0117] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment time was changed to 60 minutes in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0118] [Example 4]
[0119] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment temperature was changed to 20°C in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0120] [Example 5]
[0121] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment temperature was changed to 70°C in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0122] [Example 6]
[0123] As shown in Table 1, a sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1. A coating film was prepared in the same manner as in Example 1, except that the amount of aqueous silica sol was changed to 1 part relative to 9 parts of sol solution. Evaluation was then performed. The results are shown in Table 4.
[0124] [Example 7]
[0125] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, acetic acid was added dropwise to achieve a concentration of 0.7% in the organic acid addition step. A coating film was prepared in the same manner as in Example 1, except that a mixture was used in which the amount of aqueous silica sol was changed to 9 parts relative to 1 part sol solution. The results were then evaluated. The results are shown in Table 4.
[0126] [Example 8]
[0127] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 0.02%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0128] <Contraction Steps>
[0129] A solution of 4.0 parts of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 20.8 parts of 2-propanol (water-soluble organic solvent), and 0.8 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0130] Subsequently, a solution obtained by mixing 0.3 parts of 0.01N hydrochloric acid (inorganic acid), 48.6 parts of 2-propanol (water-soluble organic solvent), and 30.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0131] [Example 9]
[0132] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 20%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0133] <Contraction Steps>
[0134] 40.0 parts of a solution of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 10.8 parts of 2-propanol (water-soluble organic solvent) and 7.8 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel and a stirring device, and the contents were stirred at 130 rpm.
[0135] Subsequently, a solution obtained by mixing 2.6 parts of 0.01N hydrochloric acid (inorganic acid), 25.2 parts of 2-propanol (water-soluble organic solvent), and 18.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0136] [Example 10]
[0137] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 0.02%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0138] <Contraction Steps>
[0139] A solution of 4.0 parts of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 20.7 parts of 2-propanol (water-soluble organic solvent), and 0.8 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0140] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 48.4 parts of 2-propanol (water-soluble organic solvent), and 29.9 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0141] [Example 11]
[0142] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 20%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0143] <Contraction Steps>
[0144] 40.0 parts of a solution of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 11.1 parts of 2-propanol (water-soluble organic solvent) and 7.8 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel and a stirring device, and the contents were stirred at 130 rpm.
[0145] Subsequently, a solution obtained by mixing 1.0 part of 0.01N hydrochloric acid (inorganic acid), 26.0 parts of 2-propanol (water-soluble organic solvent) and 18.5 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0146] [Example 12]
[0147] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment temperature was changed to 10°C in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0148] [Example 13]
[0149] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment time was changed to 3 minutes in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0150] [Example 14]
[0151] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the heat treatment time was changed to 90 minutes in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0152] [Example 15]
[0153] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 0.02%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0154] <Contraction Steps>
[0155] A solution of 3.0 parts of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 21.1 parts of 2-propanol (water-soluble organic solvent), and 0.6 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0156] Subsequently, a solution obtained by mixing 0.2 parts of 0.01N hydrochloric acid (inorganic acid), 49.2 parts of 2-propanol (water-soluble organic solvent), and 30.4 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0157] [Example 16]
[0158] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 20%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0159] <Contraction Steps>
[0160] A solution of 50.0 parts of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 8.0 parts of 2-propanol (water-soluble organic solvent), and 9.7 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0161] Subsequently, a solution obtained by mixing 3.3 parts of 0.01N hydrochloric acid (inorganic acid), 18.7 parts of 2-propanol (water-soluble organic solvent) and 14.7 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0162] [Example 17]
[0163] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 15, except that, as shown in Table 1, acetic acid was added dropwise in the organic acid addition step to change the concentration to 0.002%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0164] [Example 18]
[0165] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 16, except that, as shown in Table 1, acetic acid was added dropwise in the organic acid addition step to change the concentration to 30%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0166] [Example 19]
[0167] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 0.002%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0168] <Contraction Steps>
[0169] A solution of 3.0 parts of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 21.0 parts of 2-propanol (water-soluble organic solvent), and 0.6 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0170] Subsequently, a solution obtained by mixing 0.8 parts of 0.01N hydrochloric acid (inorganic acid), 48.9 parts of 2-propanol (water-soluble organic solvent), and 30.2 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0171] [Example 20]
[0172] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 30%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0173] <Contraction Steps>
[0174] A solution of 50.0 parts of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 8.5 parts of 2-propanol (water-soluble organic solvent), and 9.7 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0175] Subsequently, a solution obtained by mixing 0.8 parts of 0.01N hydrochloric acid (inorganic acid), 19.9 parts of 2-propanol (water-soluble organic solvent), and 15.4 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0176] [Example 21]
[0177] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the organic acid was changed to formic acid in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0178] [Example 22]
[0179] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the organic acid was changed to lactic acid in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0180] [Example 23]
[0181] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the organic acid was changed to citric acid in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. The results were then evaluated.
[0182] [Example 24]
[0183] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the organic acid was changed to malic acid in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. The results were then evaluated.
[0184] [Example 25]
[0185] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 1, the organic acid was changed to succinic acid in the organic acid addition step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 4.
[0186] [Example 26]
[0187] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0188] <Contraction Steps>
[0189] 8.0 parts of tetramethoxyzirconium (metal alkoxide), 21.0 parts of 2-propanol (water-soluble organic solvent) and 3.3 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel and a stirring device, and the contents were stirred at 130 rpm.
[0190] Subsequently, a solution obtained by mixing 1.1 parts of 0.01N hydrochloric acid (inorganic acid), 49.1 parts of 2-propanol (water-soluble organic solvent) and 30.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0191] [Example 27]
[0192] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0193] <Contraction Steps>
[0194] 8.0 parts of tetraethoxyzirconium (metal alkoxide), 19.8 parts of 2-propanol (water-soluble organic solvent), and 2.6 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0195] Subsequently, a solution obtained by mixing 0.9 parts of 0.01N hydrochloric acid (inorganic acid), 46.2 parts of 2-propanol (water-soluble organic solvent), and 28.4 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0196] [Example 28]
[0197] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0198] <Contraction Steps>
[0199] 8.0 parts of tetra-n-propoxyzirconium (metal alkoxide), 19.0 parts of 2-propanol (water-soluble organic solvent), and 2.1 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0200] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 44.4 parts of 2-propanol (water-soluble organic solvent), and 27.2 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0201] [Example 29]
[0202] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0203] <Contraction Steps>
[0204] 8.0 parts of tetraisopropoxyzirconium (metal alkoxide), 19.0 parts of 2-propanol (water-soluble organic solvent) and 2.2 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel and a stirring device, and the contents were stirred at 130 rpm.
[0205] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 44.4 parts of 2-propanol (water-soluble organic solvent), and 27.2 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0206] [Example 30]
[0207] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0208] <Contraction Steps>
[0209] 8.0 parts of tetraisobutoxyzirconium (metal alkoxide), 18.4 parts of 2-propanol (water-soluble organic solvent), and 1.8 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel including a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0210] Subsequently, a solution obtained by mixing 0.6 parts of 0.01N hydrochloric acid (inorganic acid), 43.0 parts of 2-propanol (water-soluble organic solvent), and 26.4 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0211] [Example 31]
[0212] A sol solution containing a particulate incomplete condensate of aluminum alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0213] <Contraction Steps>
[0214] 8.0 parts of aluminum trisec-butoxy (metal alkoxide), 20.3 parts of 2-propanol (water-soluble organic solvent), and 2.9 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0215] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 47.5 parts of 2-propanol (water-soluble organic solvent), and 29.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0216] [Example 32]
[0217] A sol solution containing a granular incomplete condensate of niobium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0218] <Contraction Steps>
[0219] 8.0 parts of niobium pentabutoxy (metal alkoxide), 17.9 parts of 2-propanol (water-soluble organic solvent), and 1.5 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0220] Subsequently, a solution obtained by mixing 0.5 parts of 0.01N hydrochloric acid (inorganic acid), 41.8 parts of 2-propanol (water-soluble organic solvent), and 25.6 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0221] [Example 33]
[0222] A sol solution containing a granular incomplete condensate of tungstate alkoxide was obtained in the same manner as in Example 1, except that the condensation step and the organic acid addition step were changed as described below, as shown in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0223] <Contraction Steps>
[0224] 8.0 parts of ethoxytungsten (V) (metal alkoxide), 18.2 parts of 2-propanol (water-soluble organic solvent), and 1.7 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0225] Subsequently, a solution obtained by mixing 0.6 parts of 0.01N hydrochloric acid (inorganic acid), 42.5 parts of 2-propanol (water-soluble organic solvent), and 26.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0226] <Organic Acid Addition Steps>
[0227] While stirring the reaction solution after the condensation step at 130 rpm, 12.2 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were added, followed by dropwise addition of acetic acid (an organic acid) to bring the concentration to 5%. Under continued stirring, the solution was heat-treated in an oil bath at 30°C for 30 minutes. This yielded a sol solution containing granular incomplete condensates of tungstate alkoxides.
[0228] [Example 34]
[0229] A sol solution containing a granular incomplete condensate of tantalum alkoxide was obtained in the same manner as in Example 1, except that the condensation step and the organic acid addition step were changed as described below, as shown in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0230] <Contraction Steps>
[0231] 8.0 parts of tantalum pentaethoxy (metal alkoxide), 18.3 parts of 2-propanol (water-soluble organic solvent), and 1.7 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0232] Subsequently, a solution obtained by mixing 0.6 parts of 0.01N hydrochloric acid (inorganic acid), 42.6 parts of 2-propanol (water-soluble organic solvent), and 26.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0233] <Organic Acid Addition Steps>
[0234] While stirring the reaction solution after the condensation step at 130 rpm, 12.2 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were added, followed by dropwise addition of acetic acid (organic acid) to change the concentration to 5%. Under continued stirring, a heat treatment was performed in an oil bath at 30°C for 30 minutes. This yielded a sol solution containing granular incomplete condensates of tantalum alkoxide.
[0235] [Example 35]
[0236] A sol solution containing a granular incomplete condensate of tantalum alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 2, the condensation step was changed as described below, and in the organic acid addition step, acetic acid was added dropwise to change the concentration to 5%. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0237] <Contraction Steps>
[0238] 8.0 parts of tantalum pentaethoxy (metal alkoxide), 18.3 parts of 2-propanol (water-soluble organic solvent), and 13.9 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were loaded into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0239] Subsequently, a solution obtained by mixing 0.6 parts of 0.01N hydrochloric acid (inorganic acid), 42.6 parts of 2-propanol (water-soluble organic solvent), and 26.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0240] [Example 36]
[0241] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 2. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0242] <Contraction Steps>
[0243] 10.0 parts of a solution of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 20.0 parts of 2-propanol (water-soluble organic solvent), and 2.4 parts of 3,5-dimethyl-2,4-hexanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel, and a stirring device, and the contents were stirred at 130 rpm.
[0244] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 46.8 parts of 2-propanol (water-soluble organic solvent), and 29.4 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 70°C.
[0245] [Example 37]
[0246] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, the inorganic acid was changed to sulfuric acid in the condensation step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0247] [Example 38]
[0248] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, the inorganic acid was changed to citric acid or nitric acid in the condensation step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0249] [Example 39]
[0250] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, the inorganic acid was replaced with phosphoric acid in the condensation step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0251] [Example 40]
[0252] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, 2-propanol was replaced with methanol in the condensation step, and the reaction was carried out in an oil bath while maintaining the temperature at 60°C. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0253] [Example 41]
[0254] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, 2-propanol was replaced with ethanol in the condensation step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0255] [Example 42]
[0256] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, 2-propanol was replaced with 1-propanol in the condensation step. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0257] [Example 43]
[0258] As shown in Table 3, in the condensation step, 2-propanol was replaced with ethyl cellosolve, and the reaction was carried out while maintaining a temperature of 105°C in an oil bath. In the organic acid addition step, the heat treatment temperature was changed to 100°C. Except as described above, a sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1. Furthermore, a coating film was prepared in the same manner as in Example 1. The results were then evaluated. The results are shown in Table 5.
[0259] [Example 44]
[0260] As shown in Table 3, in the condensation step, 2-propanol was replaced with butylcarbitol, and the reaction was carried out while maintaining a temperature of 105°C in an oil bath. In the organic acid addition step, the heat treatment temperature was changed to 120°C. Except as described above, a sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1. Furthermore, a coating film was prepared in the same manner as in Example 1. The results were then evaluated. The results are shown in Table 5.
[0261] [Comparative Example 1]
[0262] As shown in Table 3, the condensation step was changed as described below. Furthermore, the coated film was prepared in the same manner as in Example 1. The results were then evaluated. The results are shown in Table 5. The composition at the point where the condensation step was stopped is shown in the "Organic Acid Addition Step" column of Table 3.
[0263] <Contraction Steps>
[0264] 10.0 parts of a solution of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide) and 19.1 parts of 2-propanol (water-soluble organic solvent) were placed into a reaction vessel equipped with a thermometer, a dropping funnel and a stirring device, and the contents were stirred at 130 rpm.
[0265] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid), 44.7 parts of 2-propanol (water-soluble organic solvent), and 28.1 parts of 1-ethoxy-2-propanol (water-soluble organic solvent) was added dropwise over 30 minutes with stirring. The mixture was then allowed to react in an oil bath while maintaining the temperature at 70°C. However, precipitation occurred midway through the reaction, thus halting the reaction.
[0266] [Comparative Example 2]
[0267] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that the condensation step was changed as described in Table 3. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5.
[0268] <Contraction Steps>
[0269] 10.0 parts of a solution of tetra-n-butoxyzirconium in butanol (concentration of tetra-n-butoxyzirconium: 85 wt%, metal alkoxide), 19.1 parts of 2-ethyl-1-butanol (water-insoluble organic solvent) and 1.9 parts of 3-methyl-2,4-pentanedione (α-substituted β-diketone) were placed into a reaction vessel equipped with a thermometer, a dropping funnel and a stirring device, and the contents were stirred at 130 rpm.
[0270] Subsequently, a solution obtained by mixing 0.7 parts of 0.01N hydrochloric acid (inorganic acid) and 72.7 parts of 2-ethyl-1-butanol (water-insoluble organic solvent) was added dropwise over 30 minutes with stirring, and the mixture was then allowed to react for 2 hours in an oil bath while maintaining the temperature at 105°C.
[0271] [Comparative Example 3]
[0272] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, the organic acid addition step was not performed. Furthermore, a coating film was prepared in the same manner as in Example 1. Evaluation was then conducted. The results are shown in Table 5. The composition at the completion of the condensation step is shown in the "Organic Acid Addition Step" column of Table 3.
[0273] [Comparative Example 4]
[0274] A sol solution containing a granular incomplete condensate of zirconium alkoxide was obtained in the same manner as in Example 1, except that, as shown in Table 3, sulfuric acid was added instead of the organic acid in the organic acid addition step. Furthermore, the coating film was prepared in the same manner as in Example 1. Evaluation was then performed. The results are shown in Table 5. Descriptions of sulfuric acid are shown in the column for organic acids in Table 3.
[0275]
[0276]
[0277]
[0278]
[0279] Table 4
[0280]
[0281] Table 5
[0282]
[0283] As shown in Tables 4 and 5, the sol solutions of Examples 1 to 44 exhibit small particle sizes of the incompletely condensed particulates, resulting in excellent dispersion stability. Furthermore, the sol solutions of Examples 1 to 44 can be mixed with aqueous sol solutions in any proportion, thus enabling the formation of coating films with excellent applyability and uniformity.
[0284] By combining the sol solution of the present invention with various existing aqueous sol solutions, it is even possible to provide a uniform composite inorganic oxide film with good coating properties.
[0285] According to the present invention, the dispersion stability is excellent even when the sol solution contains water. Therefore, a sol solution that can be mixed with various aqueous sol solutions in any proportion can be provided, and composite inorganic oxide films can be easily prepared on various substrates even by a coating process. Furthermore, according to the present invention, a coating film with excellent applyability and uniformity can be provided.
[0286] While the invention has been described with reference to exemplary embodiments, it should be understood that the invention is not limited to the disclosed exemplary embodiments. The scope of the following claims should be interpreted in the broadest possible sense to cover all such modifications and equivalent structures and functions.
Claims
1. A sol solution comprising: Metal alkoxide condensates; α-substituted β-diones; and Water-soluble organic solvents The sol solution also contains inorganic acids and organic acids. in, The metal element content, inorganic acid content, organic acid content, and α-substituted β-diketone content of the metal alkoxide condensate satisfy the following relationship: 4.0×10 -5 ≤b / a≤3.5×10 -4 (1) 0.020≤c≤20 (2) 0.025≤c / a≤3.3 (3) 0.20≤a / d≤1.1 in: "a" indicates the metal element content of the metal alkoxide condensate relative to the total amount of the sol, expressed as a percentage by mass. "b" indicates the content of inorganic acid relative to the total amount of the sol, expressed as a percentage by mass. "c" indicates the content of organic acids relative to the total amount of the sol, expressed as a percentage by mass; and "d" indicates the content of α-substituted β-dione relative to the total amount of the sol, expressed as a percentage by mass. The sol solution is prepared by a method comprising: a condensation step in which a metal alkoxide is condensed by: adding an inorganic acid to a reaction solution obtained by mixing the metal alkoxide and an α-substituted β-diketone with a water-soluble organic solvent; and an organic acid addition step in which an organic acid is added to the reaction solution after the condensation step.
2. The sol solution according to claim 1, wherein the organic acid is an organic acid having one or more carboxyl groups and having 6 or fewer carbon atoms.
3. The sol solution according to claim 2, wherein the organic acid comprises at least one selected from the group consisting of acetic acid; formic acid; citric acid; malic acid; lactic acid; succinic acid; propionic acid; glycolic acid; malonic acid; glutaric acid; and tartaric acid.
4. The sol solution according to any one of claims 1-3, wherein the inorganic acid comprises at least one selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.
5. The sol solution according to any one of claims 1-3, wherein the water-soluble organic solvent comprises at least one selected from: alcohol solvents; glycol solvents; glycol ether solvents; ether solvents; and ketone solvents.
6. The sol solution according to any one of claims 1-3, wherein the water-soluble organic solvent is contained in an amount of 40% by mass or more relative to the total amount of the sol solution.
7. The sol solution according to any one of claims 1-3, wherein the α-substituted β-diketone is 3-methyl-2,4-pentanedione.
8. The sol solution according to any one of claims 1-3, wherein the median diameter of the metal alkoxide condensate is 1 nm or more and 100 nm or less.
9. A mixture comprising: The sol solution according to claim 1, and water, The pH value of the mixture is above 2.00 and below 7.
00.
10. The mixture according to claim 9, The metal alkoxide condensate in the sol solution contains a first metal element, and The mixture further includes a metal alkoxide condensate containing a second metal element different from the first metal element.
11. A coated film, said coated film being obtained by heating one of the following: The sol solution according to any one of claims 1-3, or The mixture according to claim 9 or 10.
12. A method for preparing a sol solution, comprising: The condensation step of condensing a metal alkoxide involves adding an inorganic acid to a reaction solution obtained by mixing the metal alkoxide and an α-substituted β-diketone with a water-soluble organic solvent; and An organic acid addition step, in which an organic acid is added to the reaction solution after the condensation step; and The step of obtaining the sol solution according to claim 1 after the organic acid addition step.
13. The method for preparing a sol solution according to claim 12, wherein the organic acid addition step comprises: After adding organic acids, heat treatment is performed by heating at 20°C to 100°C for 5 minutes to 1 hour.
14. A method for preparing a coated film, the method comprising, in the following order: The application step of applying the sol solution according to any one of claims 1-3 or the mixture according to claim 9 or 10 to a substrate. The heating step involves heating the substrate at a temperature equal to or lower than its glass transition temperature.
Citation Information
Patent Citations
Coating solution for forming bismuth-based ferroelectric substance thin film and ferroelectric substance thin film and ferroelectric substance memory using the same
JP1998259007A
Metal oxide nanoparticle, method for producing the same, light-emitting element assembly, and optical material
JP2007051053A
Zirconia sol
JP2011073893A
Coating solutions for use in forming bismuth-based ferroelectric thin films, and ferroelectric thin films, ferroelectric capacitors and ferroelectric memories formed with said coating solutions, as well as processes for production thereof
US20010010867A1
